The dynamics of a long-lasting effusive eruption modulated by Earth tides - Dumont, Stéphanie; Le Mouël, Jean-Louis; Courtillot, Vincent; Lopes, Fernando; Sigmundsson, Freysteinn; Coppola, Diego; Eibl, Eva P. S.; Bean, Christopher J. (Earth and Planetary Science Letters, 2020)
International audience Deciphering eruptive dynamics in near-real time is essential when dealing with hazard assessment and population evacuation. Recognition of specific patterns in time-series measured during volcanic activity may help decipher distinctive behavior at active volcanoes, providing insights into the underlying driving mechanisms. Multi-parameter data sets usually agree on the overall trend characterizing the temporal evolution of an eruption providing insights into the first-order eruptive dynamics. However, second-order variations detected in different data sets remain often poorly understood. The 2014-2015 Holuhraun eruption (Iceland) offers an excellent opportunity to investigate the dynamics of a long-lasting effusive eruption. We analyze the seismic tremor and the volcanic radiated power emitted by the lava field during the 6 months of the eruption using Singular Spectrum Analysis (SSA). In both geophysical time-series, we identify periods from ∼5 to ∼32 days coinciding with periods of Earth tides. Here we show that ∼50% of both signals are composed of tidal periods suggesting that magma movements follow frequencies imposed by lunisolar forces within the crust and at Earth's surface.